2017
DOI: 10.3389/fphys.2017.00677
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hypobaric Hypoxia Modulates Primary Cilia Differently in Adult and Fetal Ovine Kidneys

Abstract: Hypoxic environments at high altitude have significant effects on kidney injury. Following injury, renal primary cilia display length alterations. Primary cilia are mechanosensory organelles that regulate tubular architecture. The effect of hypoxia on cilia length is still controversial in cultured cells, and no corresponding in vivo study exists. Using fetal and adult sheep, we here study the effect of chronic hypobaric hypoxia on the renal injury, intracellular calcium signaling and the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…On the one hand, staying at plateau areas caused liver dysfunction through endoplasmic reticulum stress and subsequent apoptosis, decreased expression content of hepatic microsomal enzyme, and might also be related to the enzyme's activity changes ( 22 , 23 ). On the other hand, exposure to high-altitude exerted significant effects on kidney injury by the alteration of cilia length and function which was resulted from the renal hypoperfusion caused by the chronic hypobaric hypoxic environment ( 24 , 25 ). Taking together, TBI and high-altitude jointly lead to the liver and renal injury through a series of complicated mechanisms, which may provide basics for treatment and should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, staying at plateau areas caused liver dysfunction through endoplasmic reticulum stress and subsequent apoptosis, decreased expression content of hepatic microsomal enzyme, and might also be related to the enzyme's activity changes ( 22 , 23 ). On the other hand, exposure to high-altitude exerted significant effects on kidney injury by the alteration of cilia length and function which was resulted from the renal hypoperfusion caused by the chronic hypobaric hypoxic environment ( 24 , 25 ). Taking together, TBI and high-altitude jointly lead to the liver and renal injury through a series of complicated mechanisms, which may provide basics for treatment and should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that the effect of hypoxic conditions on PC formation, length and function is a little complicated with cell type and developmental stage. The percent of elongated cilia reduced significantly in rat tail tendon fascicles under hypoxic conditions, but the cilia length and function increased in the hypoxic fetal proximal and distal collecting epithelia [ 62 , 63 ]. It might be due to many other molecular changes as well as HIF-1α under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Cilia turnover is intrinsically linked to cell cycle progression and cell growth conditions such as starvation and hypoxia. [28][29][30] Alterations of ciliary dynamics under pathological conditions can influence cell fate choices and tissue homeostasis. 31 Third, we have not determined the impact of Kif3a T674A mutation on organ systems other than lung, skeleton, and brain.…”
Section: Discussionmentioning
confidence: 99%